2016
DOI: 10.1515/jim-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Biomarkers of Vulnerable Coronary Plaques

Abstract: An unstable plaque has a high risk of thrombosis and at the same time for a fast progression of the stenosis degree. Also, “high-risk plaque” and “thrombosis-prone plaque” are used as synonym terms for characterization of a vulnerable plaque. The imaging biomarkers for vulnerable coronary plaques are considered to be spotty calcifications, active remodeling, low-density atheroma and the presence of a ring-like attenuation pattern, also known as the napkin-ring sign. Computed cardiac tomography can determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…FFR-CT is calculated from standard CTA datasets being able to provide relevant information of functional relevance of a plaque. Several recent studies suggested that FFR is significantly lower in unstable plaques as compared to stable ones with the same anatomical severity [3]. In a retrospective analysis of the images scanned with 1 year prior to an AMI, FFR-CT was lowest and APS was highest in the segments located upstream of the maximum stenosis [24,25].…”
Section: Computational Flow Dynamics For Calculation Of Essmentioning
confidence: 99%
See 1 more Smart Citation
“…FFR-CT is calculated from standard CTA datasets being able to provide relevant information of functional relevance of a plaque. Several recent studies suggested that FFR is significantly lower in unstable plaques as compared to stable ones with the same anatomical severity [3]. In a retrospective analysis of the images scanned with 1 year prior to an AMI, FFR-CT was lowest and APS was highest in the segments located upstream of the maximum stenosis [24,25].…”
Section: Computational Flow Dynamics For Calculation Of Essmentioning
confidence: 99%
“…The most sensitive biomarkers associated with plaque vulnerability differ largely according to the imaging technique used for assessment of VP. While computed tomographic angiography (CTA) imaging has a definite role in visualization of several vulnerability features such as positive remodeling, napkin ring sign, spotty calcifications or very low density plaques appearing as dark spots on CTA images, its value remains low in assessing the thickness of the fibrous cap, mainly due to the insufficient resolution [3]. Intravascular imaging techniques, namely intravascular ultrasound (IVUS) and optical coherence tomography (OCT) have been proposed to represent efficient alternatives to CTA imaging for detecting thin cap fibroatheroma as well as for quantification of plaque components [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most important CT vulnerability markers at this time are the volume of low density atheroma, the plaque burden, the thin fibrous cap, and the positive remodeling. [1][2][3][4] So the main question today remains: is it possible to define a new vulnerability marker based on the CT images, and, more importantly, would it be possible for shear stress to become that new vulnerability marker?It is known that shear stress plays an important role in the development of atherosclerosis, 5-7 through complex processes that are more and more better known with the help of computer fluid dynamics. [8][9][10][11][12] There were also several successful attempts of finding the correlation between shear stress and other vulnerability factors, defined by the use of invasive imagUnauthenticated Download Date | 5/12/18 9:06 AM…”
mentioning
confidence: 99%
“…The most important CT vulnerability markers at this time are the volume of low density atheroma, the plaque burden, the thin fibrous cap, and the positive remodeling. [1][2][3][4] So the main question today remains: is it possible to define a new vulnerability marker based on the CT images, and, more importantly, would it be possible for shear stress to become that new vulnerability marker?…”
mentioning
confidence: 99%
“…1 However, the description of morphological features associated with vulnerable plaques cannot serve as a decision tool in the absence of clear data regarding their hemodynamic impact, which is the key determinant of myocardial ischemia.…”
mentioning
confidence: 99%